Factors Affecting the Pre-service Student Teachers’ Performance in Implementing the Questioning Skills in their Microteaching Practices - Trisna Helda; Sri Imelwaty; Wahyudi Rahmat (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2021)
before they undergo the real teaching practices at schools. To this end, the study aims are to explore the factors which affecting the pre-service student teachers’ performance in implementing the questioning skills during their microteaching practices. This study employed a case study research design by collecting qualitative data. A small group consisting of 32 pre-service student teachers was interviewed regarding what things affecting their performance in implementing the questioning skills when teaching Bahasa Indonesia, the official language of Indonesia, during their microteaching practices. Thematic analysis was conducted for analyzing the qualitative data. The findings show the internal and external factors affecting their performance in implementing the questioning skills during their microteaching practices. The study findings could inform the improvement of the microteaching practices to increase the pre-service student teachers’ performances